Pedro António Janeiro (Editor). Drawing (...) City (...) Body, Dwelling on Earth. Imagined-Architectures: architectural graphic representation and other images (diségno, 2019)
Firstly, what is the body? The definition of fluctuating signifier given by structuralist ethnologists, and especially Lévi-Strauss [Lévi-Strauss 1965], is  powerful in arguing the linguistic evanescence that no approach, meaning, metaphorical use, can force or block. A mediator between codes who violently imposes its ability to “exercise symbolic thought”. One could say that the body does not mean anything but it speaks the language of others, it is trans-formed, allowing to trans-late various codes, to enter through a passe-partout in different levels (natural, artificial, abstract, ...). (read more)